SHAKESPEARE’S SONNETS AND THE CONCEPT OF TIME - Dilafruz To’raqulova (International Journal Of Literature And Languages, 2024)
Shakespeare's sonnets actually follow a basic structure based on time. In this article, we have considered the concept of time in Shakespeare's sonnets.